2022
DOI: 10.1021/acsaem.1c03419
|View full text |Cite
|
Sign up to set email alerts
|

Effectively Tuning the Ratio of CO and H2 into Syngas through CO2 Electrochemical Reduction over a Wide Potential Range on a ZnO Nanosheet via Ni Doping

Abstract: Electrochemical CO2 reduction (ECR) into syngas is a promising method to reduce CO2 in the atmosphere. However, balancing the activity of ECR and hydrogen evolution reaction (HER) and controlling the stable CO/H2 ratios in a large potential range for the industrial desired syngas are still challenging. Herein, a low-cost Ni-doped ZnO nanosheet array on a zinc foil is synthesized via a convenient hydrothermal method to produce a controllable ratio of CO/H2 into syngas. Because of the lower impedance and larger … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…The lower FE CO and j CO (−60 mA cm −2 at −1.2 vs RHE) were recorded for the Fe-ZnO. These ECR characteristics were associated with the known high activity of Fe for HER, 46,47 along with the diminishment of active ZnO sites owing to the uniform distribution of Fe-oxide (Figure 3). A similarly low ECR performance toward CO is seen by the Ni-ZnO and Co-ZnO gas diffusion electrodes (GDEs) (Figure 4F).…”
Section: ■ Results and Discussionmentioning
confidence: 86%
“…The lower FE CO and j CO (−60 mA cm −2 at −1.2 vs RHE) were recorded for the Fe-ZnO. These ECR characteristics were associated with the known high activity of Fe for HER, 46,47 along with the diminishment of active ZnO sites owing to the uniform distribution of Fe-oxide (Figure 3). A similarly low ECR performance toward CO is seen by the Ni-ZnO and Co-ZnO gas diffusion electrodes (GDEs) (Figure 4F).…”
Section: ■ Results and Discussionmentioning
confidence: 86%
“…In contrast, the ratio of H 2 and CO in the CO 2 RR product syngas was progressively regulated from 102 to 0.07 along with the increment of the reaction temperature from 100 to 300 °C, covering the entire ratio range of H 2 /CO where syngas can serve as industrial feedstocks. [28] We believe our current work could pave a novel route to fully utilize the thermo-photogenerated electrons and holes in one redox cycle for effective solar energy conversion, carbon emission reduction, as well as valueadded chemicals and fuel production. Also, the exciting discovery of the temperature-selectivity relation is expected to be inspiring for the follow-up works in the field of photothermal catalysis.…”
Section: Introductionmentioning
confidence: 91%
“…The environmental crisis has gained global attention with the ever-increasing CO 2 emissions caused by the over-consumption of fossil fuels. [1][2][3][4] Within this context, reducing CO 2 into value-added chemicals, such as CO, CH 4 , CH 3 OH, or syngas through photocatalysis, [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] thermocatalysis, [25][26][27] and electrocatalysis [28][29][30][31][32] is of great environmental, energy, and economic interests. Especially, photocatalysis, an environmentally friendly and recyclable process, has become the worldwide research focus on the promotion of CO 2 reduction reaction (CO 2 RR).…”
Section: Introductionmentioning
confidence: 99%
“…Some previous reports have shown that doping Ni in a metallic oxide can enhance the properties of the HER. 148,149 So, Wang et al 150 introduced Ni into ZnO nanosheets to produce a controllable ratio of CO/H 2 syngas over a large potential range. Because of small charge resistance and large electrochemical area, the Ni-doped ZnO prepared had a more significant current density than that of pure ZnO (Fig.…”
Section: The Zno-based Catalystsmentioning
confidence: 99%
“…The Electrochemical Society ("ECS"). ( j) Nyquist plots and (k) C dl plotted with different scanning rates for ZnO, ZnO-Ni 1 , ZnO-Ni 2 , and ZnO-Ni 3 on a Zn foil in 0.1 M KHCO 3 , respectively 150. Copyright 2022.…”
mentioning
confidence: 99%